Artificial Intelligence in India: Laws & Flaws (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Artificial Intelligence is a new concept. The emergence of aftificial Intelligence has reached to all aspect of human life. This is particulary important in domain their accountability and legal compliance are crutial, such as healthcare, finance and legal systems. Explainable models enable individuals to comprehend how decisions are reached, evaluate the reliability of the outputs, and potentially challenge or seek redress in case of errors or harmful outcomes. Promoting transparency and encouraging the development of explainable Artificial Intelligence involves a combination of technical approaches, regulatory guidance, and industry standards. Organizations should adopt practices that prioritize transparency and explainability in their AI development processes. Regulators and policymakers can provide guidelines and standards to promote transparency, while researchers can focus on developing techniques that enhance the explainability of AI systems.